Positive Effect of Parasitic Monoclinic Phase of Hf0.5Zr0.5O2 on Ferroelectric Endurance. (12th September 2021) - Song, Tingfeng; Estandía, Saúl; Tan, Huan; Dix, Nico; Gàzquez, Jaume; Fina, Ignasi; Sánchez, Florencio
Abstract: Endurance of ferroelectric HfO2 needs to be enhanced for its use in commercial memories. This work investigates fatigue in epitaxial Hf0.5 Zr0.5 O2 (HZO) instead of polycrystalline samples. Using different substrates, the relative amount of orthorhombic (ferroelectric) and monoclinic (paraelectric) phases is controlled. Epitaxial HZO films almost free of parasitic monoclinic phase suffer severe fatigue. In contrast, fatigue is mitigated in films with a greater amount of paraelectric phase. This suggests that fatigue can be intrinsically pronounced in ferroelectric HZO. It is argued that the enhancement of endurance in films showing coexisting phases results from the suppression of pinned domain propagation at ferroelectric–paraelectric grain boundaries, in contrast with a rapid increase of the size of the pinned domains in single ferroelectric regions. Abstract : Epitaxial ferroelectric Hf0.5 Zr0.5 O2 films almost free of parasitic phase exhibit strong fatigue, whereas fatigue is mitigated in films with a significant amount of parasitic paraelectric phase. It is proposed that the improvement of endurance in films showing coexisting phases results from the suppression of pinned domain propagation at ferroelectric–paraelectric grain boundaries.